Penguatan Kesadaran Pentingnya Pembiayaan Pendidikan Madrasah Diniyah Melalui Pengembangan Kapasitas Komunitas (Community Capacity Building) di Kabupaten Ciamis dan Kota Banjar Propinsi Jawa Barat - Azis, Abdul; Iswanto, Pepe; Selamet, Selamet (Khidmat, 2023)
This article is the result of community service which focuses on efforts to strengthen awareness of the importance of financing Islamic madrasah education through community capacity building in Ciamis district and Banjar City, West Java Province. So far, the community in general still prioritizes Islamic madrasah education, so that management and financing are carried out as is without any effort to improve the management system and attention from the community. The service method is carried out using several techniques, namely conducting focus group discussions, workshops, and forming a Madrasah Diniyah support group (KPMD). After providing assistance and service, the results can be seen, including the emergence of public awareness of the importance of financing education for Madrasah Diniyah and the formation of Madrasah Diniyah support groups consisting of community leaders, aghniya, ASN, entrepreneurs and other donors.